KAJIAN PRAGMATIK DALAM BAHASA ARAB (ANALISIS BENTUK DAN FUNGSI TINDAK TUTUR DIREKTIF BAHASA ARAB DALAM FILM â€œASHABUL KAHFIâ€) - Nurwendah, Yusti Dwi; Mahera, Intan Annisaul (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2019)
Pragmatics is the study of the context outside the language and the purpose of speech. This study focuses on one type of pragmatics, namely the speech act of Arabic directives in the film